2016
DOI: 10.1016/j.jvs.2014.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanosphere-guided site-specific delivery of vascular endothelial growth factor gene attenuates restenosis in rabbit balloon-injured artery

Abstract: Intra-arterial VEGF gene delivery by magnetic microspheres significantly increased DNA stability, transfection efficiency, and targeting specificity, resulting in exogenous VEGF overexpression and attenuated intimal hyperplasia in balloon-injured artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Sixteen animal model studies [27-32, 34-42, 45] reported change in arterial lumen post-VEGF modulation. Fourteen studies reported change in neointimal area proliferation (mm 2 ) [27-29, 32-37, 39, 42-45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen animal model studies [27-32, 34-42, 45] reported change in arterial lumen post-VEGF modulation. Fourteen studies reported change in neointimal area proliferation (mm 2 ) [27-29, 32-37, 39, 42-45].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 studies remained all of which were included in this systematic review (Fig. 1 ; Table 1 ) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature EC or EC progenitor cell transplantation to the injured vessel lumen [27][28][29][30][31] , or accelerating reendothelialization by VEGF or VEGF gene delivery 32,33 , may be promising to combat restenosis after balloon injury or in-stent stenosis. To compare the effect of ECs and arterial flow on vascular remodeling, we seeded HUVECs in the lumen of rat aortas and human umbilical arteries immediately after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic use of ECs, or elements of their secretome, may be an effective biological approach to treat vascular injuries caused by the aforementioned interventions. In animal models, local delivery of endothelial or endothelial progenitor cells to the injury site [27][28][29][30][31] , injection of intra-arterial VEGF 32 or VEGF gene delivery 33 , all result in reduction of intimal hyperplasia after balloon injury in animal models. However, all of these studies employ animal models that are not ideally representative of human physiology.…”
Section: Introductionmentioning
confidence: 99%